Impact of Momordica Charantia (Karela) on the Proportion of Hepatocytes with Intranuclear Inclusions in the StreptozotocinInduced Diabetic Rats (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Momordica charantia has some hypoglycemic properties.Objective: The purpose of the present study was to find out the impact of Momordica charantia (karela) on the proportion of hepatocytes in the  Streptozotocin-induced  diabetic  rats.Methodology: This  was  an  animal  study  carried  out  in  the Department of Anatomy at Bangabandhu Sheikh Mujib Medical University (BSMMU) and Bangladesh Institute of Research & rehabilitation in Diabetes, Endocrine & metabolic Disorders (BIRDEM), Dhaka. Healthy young Long Evans rats of male sex weighing 150 to 280gm with an age range of 10 to 12 weeks were used in this study. The rats were divided into 4 equal groups depending upon their different sorts of dietary feedings and drug treatment. The variation of different proportion of hepatocytes with intranuclear inclusions in different groups of rat was monitored.Result: Sixty five rats were included in this study. Mean proportion of hepatocytes with intranuclear inclusions on day 51 from Streptozotocin/vehicle injection in the control group which was known as Group-A was 0. In untreated diabetic group the mean proportion of hepatocytes with intranuclear inclusions was 3.71 ± 0.82. On the other hand, in the insulin-treated diabetic rats the mean proportion of hepatocytes with intranuclear inclusions was 0 and in the karela-treated diabetic rats, the proportion of hepatocytes with intranuclear inclusions was 0. The value in the insulin-treated diabetic rats (p=0.0001) and in the karela-treated diabetic rats (p= 0.0001) were significantly lower than that of the untreated diabetic rats; however, there was no significant difference between the insulin-treated diabetic rats & the karela-treated diabetic rats (P>0.05) in this regard.Conclusion: Karela showed a tendency of acting against hyperglycemic effects of Streptozotocin-induced diabetes mellitus and also acting against the rise in proportion of hepatocytes with intranuclear inclusions in Streptozotocin-induced diabetes mellitus.DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20761J Shaheed Suhrawardy Med Coll, 2013;5(2):84-86